2022
DOI: 10.14218/jcth.2022.00129
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on Liver Transplant Activity in the USA: Variation by Etiology and Cirrhosis Complications

Abstract: Background and Aims:The COVID-19 pandemic has impacted the care of patients with liver disease. We examined impact of COVID-19 on liver transplant (LT) activity in the USA. Methods: LT listings in the United Network for Organ Sharing (UNOS) database (April 2018-May 2021) were analyzed to examine the impact of COVID-19 pandemic on the LT activity based on etiology: hepatitis C virus (HCV), alcohol-associated liver disease (ALD), alcoholic hepatitis (AH), and nonalcoholic steatohepatitis (NASH) complications: he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Several papers have evaluated the effect of the COVID-19 pandemic on LT, and frequently there were differences regarding increased or decreased frequency of LT seen because of different time points, different populations and also the evolving nature of the pandemic and the response to it. [6][7][8] The importance of the paper by Kuo et al 5 is that they are able, at least in this specific population, to start identifying the finer differences as to how the pandemic affected LTs of different etiology and to what extent.…”
Section: Journal Of Clinical and Translational Hepatology 2023mentioning
confidence: 99%
See 4 more Smart Citations
“…Several papers have evaluated the effect of the COVID-19 pandemic on LT, and frequently there were differences regarding increased or decreased frequency of LT seen because of different time points, different populations and also the evolving nature of the pandemic and the response to it. [6][7][8] The importance of the paper by Kuo et al 5 is that they are able, at least in this specific population, to start identifying the finer differences as to how the pandemic affected LTs of different etiology and to what extent.…”
Section: Journal Of Clinical and Translational Hepatology 2023mentioning
confidence: 99%
“…Regarding the MELD score, the main effect was seen with HCV-related LTs, where there was an increase in the average monthly MELD score by 0.7, again indicating the increased challenges for these patients. When Kuo et al 5 evaluated the effect of the COVID-19 pandemic on the frequency of LT performed for HCC and ACLF grade 2-3, the analysis found that for HCC there was a 22% monthly decrease on a log scale of LTs performed during the COVID-19 era, with recipients having higher MELD scores, an increase of 0.36% per month, and being more likely to have ALD-related ACLF, as well as receive a poorer quality graft. As far as ACLF grade 2-3 is concerned although there was a 17% monthly increase in the LTs performed in the COVID-19 era, the recipients had a higher MELD score, and the grafts were of poorer quality.…”
mentioning
confidence: 99%
See 3 more Smart Citations